Cariogenic Biofilm: Pathology-Related Phenotypes and Targeted Therapy - Xiuqin Chen; Eric Banan-Mwine Daliri; Akanksha Tyagi; Deog-Hwan Oh (Microorganisms, 2021)
The initiation and development of cariogenic (that is, caries-related) biofilms are the result of the disruption of homeostasis in the oral microenvironment. There is a daily accumulation of dental biofilm on the surface of teeth and its matrix of extracellular polymers supports the host in its defense against invading microbes, thus helping to achieve oral microbial homeostasis. However, the homeostasis can be broken down under certain circumstances such as during long-term exposure to a low pH environment which results in the dominance of acidogenic and acid-tolerating species in the dental biofilm and, thus, triggers the shift of harmless biofilm to an acidic one. This work aims to explore microbial diversity and the quorum sensing of dental biofilm and their important contributions to oral health and disease. The complex and multispecies ecosystems of the cariogenic biofilm pose significant challenges for the modulation of the oral microenvironment. Promising treatment strategies are those that target cariogenic niches with high specificity without disrupting the balance of the surrounding oral microbiota. Here, we summarized the recent advances in modulating cariogenic biofilm and/or controlling its pathogenic traits.